Tantangan Yang Dihadapi Oleh Perbankan Nasional Pada Aplikasi Financial Technology Berbasis Cashless - Ine Aprianti; Lucy Nurfadilah (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2019)
This research was made to find out the challenges faced by the National Banking on Financial Technology Applications where the rise of financial technology is growth in various aspects making it easier for users to support the needs of this modern life. Ranging from transportation services, food delivery services to house cleaning services. In this study using a questionnaire with 210 respondents. The current technological relationship is closely related to the existence of the internet as the main access. We need to know that the existence of Fintech can be one of the driving forces for the existence of a movement to help increase competition in the combination of banking technology. It is shown from the results of the study that the calculated F value of 710,596 becomes the calculated F value> F table, the significance value of 0,000 <0.005 means that there is an influence of conventional bank challenges on cashless-based fintech simultaneously. The value of t arithmetic X1 of 11.742 so the value of t arithmetic> t table, the significance value of 0,000 <0.005 means that there is an influence of conventional bank challenges on cashless-based fintech partially. The value of t count X2 of 14,193 so the value of t count> t table, the significance value of 0,000 <0.005 means that there is a partial influence of conventional bank challenges on cashless-based fintech.